Extensive Actinomycetoma Clinical Manifestations and Histopathology: A Case Report - Fifa Argentina; Rusmawardiana; Nopriyati; Putri Laksmi Karim (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Actinomycetoma is a chronic infection of cutis, subcutaneous, bone, and viscera tissue. It is characterized by sinuses containing masses of causative organisms often referred to as "grains." Actinomycetoma is caused by aerobic bacteria, and they have been misclassified as a fungal species. Diagnosis of actinomycetoma was based on clinical features and confirmation by direct examination. This study aimed to describe the clinical and histopathological features of actinomycetoma. Case presentation: A 34-year-old woman complained of a mass on her left leg that had increased in number and pain 3 months before admission to the hospital with a history of trauma. Regio pedis sinistra has trias mycetoma, such as edema (swelling), multiple sinuses, and grain with hypertrophic scars. Histopathological with fibro collagenous connective tissue, moderate to dense diffuse PMN inflammatory cells, plasma cells, lymphocytes, hemosiderophages, multinucleated giant cells, epithelioid cells, and microorganisms. In periodic acid Schiff (PAS) there is the Splendore-Hoeppli phenomenon. Conclusion: Diagnosis of actynomycetoma was confirmed by the mycetoma triad and the Splendore-Hoeppli phenomenon. Actinomycetoma is more invasive and can cause bone destruction more quickly than eumycetoma.